Increased Serum Neutrophil Lymphocyte Ratio Raises the Risk for Peripheral Diabetic Neuropathy in Type 2 Diabetes Mellitus Patients - Anak Agung Ayu Agung Pramaswari; I Made Oka Adnyana; I Putu Eka Widyadharma; Ketut Suastika (Siriraj Medical Journal, 2023)
Objective: Peripheral diabetic neuropathy (PDN) is among the most prevalent diabetes mellitus (DM) sequelae. PDN is a severe health issue that represents a huge social and economic burden worldwide, is associated with long-term morbidity, and diminishes the quality of life of those affected. The neutrophil-lymphocyte ratio (NLR) is a mixture of the two primary components of chronic inflammatory diseases (high neutrophils and low lymphocytes) that contribute to the production of PDN. This study aimed to demonstrate high serum NRL levels enhance the risk of PDN in type 2 DM patients.